Plasma Biomarkers of Poor Muscle Quality in Older Men and Women from the Baltimore Longitudinal Study of Aging - Moaddel, Ruin; Fabbri, Elisa; Khadeer, Mohammed A; Carlson, Olga D; Gonzalez-Freire, Marta; Zhang, Pingbo; Semba, Richard D; Ferrucci, Luigi (The journals of gerontology. Series A, Biological sciences and medical sciences, 2016)
Aging is characterized by progressive decline in muscle mass, strength, and quality all of which contribute to functional impairment, falls, mobility disability, and frailty. Circulating factors may provide clues on the mechanisms for decline in muscle quality with aging. Characterizing the metabolic profile associated with reduced muscle quality in older persons could have important translational implications for the early identification of subjects at high risk of developing sarcopenia and the identification of targets for new preventive strategies and treatments. In a pilot cross-sectional, case-control study nested in the Baltimore Longitudinal Study on Aging, we compared circulating metabolites between 79 participants with low muscle quality ratio and 79 controls with high muscle quality, matched by age, sex, and height. The concentrations of 180 metabolites were determined by LC MS/MS, using the Biocrates p180 system, a targeted metabolomics approach. Participants with low muscle quality had significantly higher levels of leucine, isoleucine, tryptophan, serotonin, and methionine, while those with high muscle quality had significantly lower levels of putrescine and the selected phophatidylcholine (PCs) and lysoPCs. The results of this study open a new road for future investigations aimed at identifying new metabolic pathways involved in the decline of muscle quality with aging.